2008
DOI: 10.1007/s12010-008-8214-3
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the Efficacy of Chlorine, Chlorine Dioxide, and Ozone in the Inactivation of Cryptosporidium parvum in Water from Parana State, Southern Brazil

Abstract: In the present work, assays were performed to compare the efficacy of hypochlorous acid, chlorine dioxide, and ozone in the inactivation of Cryptosporidium oocyst in public water supply from Brazilian South conditions. Experiments were carried out in samples containing 2 x 10(4) oocysts/ml of C. parvum purified from feces of experimentally contaminated calves. An in vitro excystation method was used to evaluate oocysts' viability and to determine the inactivation rates of hypochlorous acid at 2 ppm, chlorine d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
20
0
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 39 publications
0
20
0
2
Order By: Relevance
“…However, each of the common disinfectants can produce disinfection by-products (DBPs) that can pose a threat to human health. ClO 2 has recently been used as an alternative to chlorine as it does not typically lead to the formation of toxic DBPs (Pereira et al, 2008), but it still kills bacteria efficiently and is more powerful than chlorine over a wide pH range (Pereira et al, 2008;Haas, 1990). ClO 2 does not produce significant amounts of halogenated organic DBPs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, each of the common disinfectants can produce disinfection by-products (DBPs) that can pose a threat to human health. ClO 2 has recently been used as an alternative to chlorine as it does not typically lead to the formation of toxic DBPs (Pereira et al, 2008), but it still kills bacteria efficiently and is more powerful than chlorine over a wide pH range (Pereira et al, 2008;Haas, 1990). ClO 2 does not produce significant amounts of halogenated organic DBPs.…”
Section: Introductionmentioning
confidence: 99%
“…A recent study reported that ClO 2 pre-oxidation reduced THMs and other by-products (Yang et al, 2013). In addition, ClO 2 is a more powerful bactericide than chlorine (Cl 2 ) for water treatment because of its higher oxidation capacity (Pereira et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Chlorine dioxide has been lately considered as an alternative to chlorine, since its reactions with organic or inorganic species in water do not usually lead to the formation of harmful toxic by-products [4]. In addition, chlorine dioxide (ClO 2 ) is more powerful than chlorine (Cl 2 ) as a bactericide for water treatment due to its higher oxidation capacity [5]. Chlorine dioxide accepts five electrons when reduced to chloride ion.…”
Section: Introductionmentioning
confidence: 99%
“…105 An intracellular, water-borne parasite, Cryptosporidium is notorious for its resistance to water disinfectant treatment except for ozone. 162,163 Oocysts are swallowed and undergo excystation and release sporozoites, which then attach to and are enveloped by intestinal epithelial cell membranes where they divide inside parasitophorous vacuoles within the microvillous layer, 164 outside of the cell's cytoplasm. They subsequently transform into characteristic round trophozoites.…”
Section: Cryptosporidiosismentioning
confidence: 99%